1975
DOI: 10.1139/v75-266
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Excess Kinetic Energy in the Reactions of O(1D) Atoms

Abstract: ). The effect of the excess kinetic energy of O('D) atoms on their reactions with some gaseous compounds was investigated using two different experimental methods. O('D) atoms with maximum excess kinetic energies of 41 + 5 and 31 kcal/mol respectively, were produced by flash photolysis of N 2 0 (1800-2300 A) and by photolysis of N 2 0 at 2139 A, in the presence and absence of He which is a deactivator of kinetic energy. In the first method the competition between N 2 0 and one of CO,, Xe, CO, and N2 for O('D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…It was found that addition of helium, which thermalizes kinetically hot H atoms fairly efficiently, increased the value of a/(a + ß). The effect is apparent in Figure 2 in which a/(a + ß) is plotted against the reciprocal of the helium pressure and against the average kinetic energy, {E), with which the H atoms react, calculated as described in ref 19. Neither plot is linear, but in each case a smooth curve can be extrapolated to give a/(a + ß) = 0.880 at infinite pressure of helium, cr for completely thermalized H atoms.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that addition of helium, which thermalizes kinetically hot H atoms fairly efficiently, increased the value of a/(a + ß). The effect is apparent in Figure 2 in which a/(a + ß) is plotted against the reciprocal of the helium pressure and against the average kinetic energy, {E), with which the H atoms react, calculated as described in ref 19. Neither plot is linear, but in each case a smooth curve can be extrapolated to give a/(a + ß) = 0.880 at infinite pressure of helium, cr for completely thermalized H atoms.…”
Section: Discussionmentioning
confidence: 99%
“…Ethane (99.96%) and propane (99.99%) were degassed prior to use. [6], using the flash photolysis-resonance absorption technique, measured kz(295 K) = (2.02 f 0.10) X cm3/molecule-s. This value is roughly twice that obtained in the present work, and the discrepancy is somewhat surprising in light of the good agreement between the two studies on kl(297 K).…”
Section: Experimental Techniquementioning
confidence: 99%
“…The experimental studies of the reaction (2) are restricted mainly to the problem of the reaction branching values. 1,4,6,17 The final products of both reaction channels are ground state molecules. However, the direct formation of the triplet ground state oxygen molecule in reaction channel (2) is spin forbidden, as both reaction species are in a singlet state.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental studies of the reactions (1) and (2) the excited O( 1 D) atoms are mostly produced by UV photodissociation of the N 2 O molecules. The free O( 1 D) atoms collide with the nondissociated N 2 O molecules and react with them with a near unit efficiency. , Most attention in the experimental studies has been paid to the reaction (1), as the product of this reaction, NO, is a much easier object for spectroscopic analysis than the homonuclear O 2 and N 2 molecules, the reaction (2) products. The experimental studies of the reaction (2) are restricted mainly to the problem of the reaction branching values. ,,, …”
Section: Introductionmentioning
confidence: 99%